MENGUKUR EMOTIONL LEADERSHIP PADA PIMPINAN CABANG DI PERUSAHAAN X - A. Annisa Nurul Qalbi; Rifqah Nur ridwan; RR Atika Puspita P; Wilda Ansar (Abdi Jurnal Publikasi, 2023)
Within the scope of the company, of course there will be human resources (HR) which is the most important factor so that the company's goals can be achieved. Effective leaders can manage their emotions, so that employees can trust their superiors and feel comfortable when working with them. Emotional Leadership is the ability or skill to inspire and guide employees to achieve goals, especially within the organization in order to obtain a good corporate image and better employee performance. The purpose of this study is to measure and provide evaluation to branch leaders. The method used is descriptive method according to fact finding with the right interpretation. The results of this study showed that the leadership of the Gowa 1 branch had a higher leadership attitude, followed by Gowa 2, Makassar 1 and Makassar 2. The discussion related to the survey results was used as a form of corporate evaluation to build a better corporate image and employee performance. The implications of the survey make it easy for partners to carry out further evaluations.